2012
DOI: 10.1159/000342813
|View full text |Cite
|
Sign up to set email alerts
|

Multimodality Treatment for Early-Stage Hepatocellular Carcinoma: A Bridging Therapy for Liver Transplantation

Abstract: Purpose: To evaluate the efficiency of a multimodality approach consisting of transcatheter arterial chemoembolization (TACE) and radiofrequency ablation (RFA) as bridging therapy for patients with hepatocellular carcinoma (HCC) awaiting orthotopic liver transplantation (OLT) and to evaluate the histopathological response in explant specimens. Materials and Methods: Between April 2001 and November 2011, 36 patients with 50 HCC nodules (1.4–5.0 cm, median 2.8 cm) on the waiting list for liver transplantation we… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
12
0

Year Published

2014
2014
2020
2020

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 26 publications
(12 citation statements)
references
References 74 publications
0
12
0
Order By: Relevance
“…To avoid dropout, the rate of which approaches 20%, bridging therapies may be needed [121] . Most commonly applied therapies are RFA, TACE, and surgical resection, although data from Asian countries are rather sparse.…”
Section: Very Early or Early Stagementioning
confidence: 99%
See 1 more Smart Citation
“…To avoid dropout, the rate of which approaches 20%, bridging therapies may be needed [121] . Most commonly applied therapies are RFA, TACE, and surgical resection, although data from Asian countries are rather sparse.…”
Section: Very Early or Early Stagementioning
confidence: 99%
“…PEI appears to be less efficacious than RFA, but can be chosen if the lesions are close to adjacent organs, where RFA is dangerous to perform. If the tumor size is > 3 cm, TACE or TACE plus RFA may be favored as tumors become more vascularized and the effect of RFA may be diminished [121] . Surgical resection can precede liver transplantation, and salvage transplantation can be performed in the event of recurrence, without a decrease in overall post-transplant survival [123] .…”
Section: Very Early or Early Stagementioning
confidence: 99%
“…The MELD score does not reflect disease severity or the risk for death from tumor progression, and so the points are defined as follows: 61 • HCC > 2 cm: 22 MELD points at the time of enrollment (points are added every 3 months to the waiting list, with a 10% increase in risk for death) • HCC < 2 cm: no additional points are figured in Because HCC patients are expected to be on the waiting list for more than 6 months, locoregional therapies (RFA or transarterial chemoembolization) are a good «treatment bridge» option if liver function allows it (Child-Pugh A or B). 17,60,62 Stage can be lowered provided that the aim of tumor size reduction is met, staying within the Milan or UCSF criteria. 63---65 Liver transplantation can be regarded as «salvage therapy» in patients that underwent previous liver resection and then presented with recurrence.…”
Section: Liver Transplantationmentioning
confidence: 99%
“…Recent studies have demonstrated that stereotactic body radiation therapy (SBRT) is a safe and effective treatment technique for unresectable primary and metastatic liver tumors . Liver SBRT is also recognized as a potent bridging therapy to orthotopic liver transplantation, either alone or in combination with other locoregional therapies . Given the high complexity of liver SBRT workflow and the potential risks associated with the delivery of large doses per fraction, it is important to prospectively identify weaknesses and hazards that may occur, and implement safety improvement interventions.…”
Section: Introductionmentioning
confidence: 99%
“…2,3 Liver SBRT is also recognized as a potent bridging therapy to orthotopic liver transplantation, either alone or in combination with other locoregional therapies. 4,5 Given the high complexity of liver SBRT workflow and the potential risks associated with the delivery of large doses per fraction, it is important to prospectively identify weaknesses and hazards that may occur, and implement safety improvement interventions. Task Group 100 (TG 100) of American Association of Physicist in Medicine (AAPM) recommends the ongoing use of risk-based methodologies like failure mode and effects analysis (FMEA) to supplement traditional approaches to quality management programs.…”
Section: Introductionmentioning
confidence: 99%